Antioxidant pectin enriched fractions obtained from discarded carrots (Daucus carota L.) by ultrasound-enzyme assisted extraction - Idrovo Encalada, Alondra Mariela; Perez, Carolina Daiana; Flores, Silvia K.; Rossetti, Luciana; Fissore, Eliana Noemi; Rojas, Ana Maria Luisa (2019)
Carrot residues were upgraded as pectin-enriched fractions (PEFs) useful for functional food formulation due to co-extracted antioxidants (α- and β-carotenes, lutein, α-tocopherol), and gelling effect. High power ultrasound (US)-enzyme assisted extraction was applied for efficiency and sustainability. Carrot powder (CP) in citrate-buffer (pH 5.20) was submitted to US-pretreatment (12.27 W/cm2: 20 kHz, 80% amplitude, 20 min) and a subsequent digestion (5h-40°C) without or with hemicellulase or cellulase. US-hemicellulase led to the highest PEF yield (27.1%), and extracted almost the whole pectin content of CP. US-pretreatment increased the extraction yield of all PEFs, but the existence of an additional positive effect of the following step depended on the enzyme used. PEFs contained 40-47% of UA with low DM (24-49.9%), and co-extracted antioxidants. US decreased the antioxidant contents, DM, and molecular weight, but allowed obtaining calcium crosslinked true gels, also with higher elastic modulus than non-US-extracted PEFs, being promising as food additives.